Pre-scaling up evaluation of banana technology under irrigation conditions in Abergelle District, Wag-himra Zone, Ethiopia - Wubet, A.; Assefa, N.; Mihretu, A.; Ayen, K. (International Journal of Horticultural Science, 2022)
The study was conducted to compare the improved banana technology against the local production technique to enhance demand-driven banana technology up-scaling and diffusion. Data were collected at the field and farmers' levels. Descriptive and inferential statistics, cost-benefit analysis and matrix ranking were employed for analysis. The result revealed that the average yield (38.40 ton ha-1) of improved banana technology had a significant yield advantage (47.24%) over the local practice (p